Innovative Leadership Management in Early Children Education - Moh. Ali (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
The focus of this research is to find out how the pattern of innovative leadership management in early childhood education is. The purpose of this study was to describe innovative leadership management in early childhood education. The research was conducted using a qualitative approach with the type of literature study. The process of collecting data is done by means of a literature study. This method is a literature review from various sources and relevant references. This study came to the conclusion that innovative leaders are able to complete several ideas by implementing a systematic function from planning to evaluation. There must be teamwork through creativity and team innovation, and innovative and creative ways of working and understanding actual digital information. Of course, leaders need team assistance in carrying out their duties in providing quality learning services through innovation and learning activities.